How Does Socio-Economic Status Shape a Child's Personality? - Hannah Schildberg-Hörisch; Thomas Deckers; Armin Falk; Fabian Kosse (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
We show that parental socioeconomic status (SES) is a powerful predictor of many facets of a child's personality. The facets of personality we investigate encompass time preferences, risk preferences, and altruism that are important noncognitive skills, as well as crystallized, fluid, and overall IQ that represent cognitive skills. We measure parental SES by the mother's and father's average years of education and household income. Our results show that children from families with higher SES are more patient, less likely to be risk-seeking, and score higher on IQ tests. About 20 to 40% of this relationship can be explained by dimensions of a child's environment that are shown to di ffer by parental SES: quantity and quality of time parents spend with their children, parenting style, the mother's IQ and economic preferences, a child's initial conditions at birth, and family structure. Personality profiles that vary systematically with parental SES off er an explanation for social immobility.
Keywords: J24; J13; C91; 330